Os cursos de licenciatura em música: sentido, intencionalidade e funcionalidade na educação brasileira - Lima, Flavia Albano de (2017)
This research was born from reflections that are related to the teaching of music, to its practice, to interdisciplinarity applied to Education and, more specifically, to that employed in undergraduate courses of Music in Brazil. Ambiguity was thought as a metaphor for this research, quite present in the professional trajectory of the ones Who wish to act both in the teaching ofmusic and in musical performance. The issues that have led to its implementation have given rise to the following issues: 1- How to reconcile the musical education received in the undergraduate courses of music that, in the great majority of cases, contemplate subjects directed to the learning of the musical language (pedagogical technicism), with a professional performance that extends not only for the performance but for the teaching? 2- Considering the courses and curricular bases for undergraduate courses in music, how to adapt the curricula ofthese courses in music to an interdisciplinary pedagogy, which would be able to attend, on equal terms, both the exercise ofteaching and the learning ofthe musical language? These issues have motivated the need to review the researcher's artistic performance, the musical education she has obtained and her role as coordinator and music teacher in the Music Education Course at "Grupo Educacional UNIESP". The aim of this research is focused on the Music Licensing Courses, in order to evaluate its mnction and usefulness for society and education. In order to do so, the regulations that govern these courses were analysed and testimonials from teachers were evaluated. The literature review has included texts by researchers from Education, Music Education and Interdisciplinarity. This research brings to the Academy, reflections on the importance of adopting thoughts and interdisciplinary measures in these courses as a possibility to assist music teachers both in their daily activities and in the research they produce, as well as remodeling their Educational standards. The theoretical line followed was that of a case study, with a visible bibliographical and documentary component. In addition to the Introduction and Final Considerations the thesis presents five chapters containing theoretical framework, current regulations in Education, issues on the teaching of Undergraduate courses in Music, the concept of curriculum, Interdisciplinarity, and a detailed analysis of the Undergraduate Music Course of "Grupo Educacional UNIESP